Supporting Learners’ Autonomy Through Distance Language Learning - Dameria Magdalena Sidabalok (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Computer has been widely use in all over the world. The functions of computer and modern technologies have influenced many educational institutions in developing networking language teaching learning processes that link participants from any places to join such learning processes. This situation of language learning is called distance language learning. It leads the participants or learners to be independence and responsible to their learning process, their self-assessment, self-actualization, and self-evaluation that bring them to the practices of promoting the autonomy. Thus, this paper tries to dig out how distance language learning influences language learning processes in promoting learners’ autonomy.